Urgensi Tafaqquh Fiddin dalam Meningkatkan Kemampuan Cognitif Santri Milenial - doni saputra (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2021)
Pondok Pesantren Darussalam Sumbersari is one of the educational institutions that combines formal & non-formal systems in learning or it is also called muaddalah education. This study aims to examine the activities of Tafaqquh Fiddin in improving the cognition of students in terms of Nahwu and Shorof, the factors that support and hinder and the solutions offered to improve the ability of students in understanding various literary classics. The research method used is descriptive qualitative. Data were collected by means of observation, documentation and interviews. Interviews were conducted with Asatidz MMD (Majelis Syawir Darul Falah) at the Pondok Pesantren Darussalam Sumbersari. The results showed that 1) the learning methods used were the syawir / discussion method, the question and answer method and the problem-solving method; 2) supporting factors for the implementation of Tafaqquh Fiddiin consisting of teachers / asatidz, students/students, and the cottage environment; 3) The obstacles faced are the timing of the Tafaqquh activity which is only once a week (ie on Sundays), the lack of learning media, and the background of the students.